PENERAPAN RATIONAL EMOTIVE BEHAVIOR THERAPHY UNTUK MEREDUKSI PERILAKU HEDONISME PADA SISWA KELAS XII SMA 1 BAE - Kusumaningtyas, Yuniar Mima; Santoso, Santoso; Hidayati, Richma (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The objectives achieved in this study were as follows: (1) Finding the factors that influence hedonism in SMA 1 Bae students, (2) Helping to overcome hedonism in SMA N 1 Bae students. The negative impact is seen when attending lessons, paying less attention to lessons, low learning motivation, chatting during lessons, low learning achievement. With these symptoms, researchers offer a Rational Emotive Behavior Therapy approach to reduce hedonistic behavior in SMA 1 Bae students.This research was conducted at SMA 1 Bae Kudus in the 2021/2022 academic year. The research subjects were two counselees with the initials MRZ and Indonesian citizens. Data collection techniques using interviews, observation, and documentation. The results of counselee I's research (MRZ) showed that students liked to buy things that were not needed to modify vehicles, wasting. Counselee I (MRZ) apologized to his parents, the counselee also promised to always be thrifty. Konseli II (WNI) a student likes to buy and collect expensive things. After carrying out counseling, Indonesian citizens realized that their hedonistic behavior did not benefit them. The conclusions from this study are: (1) The cause of hedonism behavior in counselee I is the counselee's high interest in automotive. The factor for counselee II is the counselee's belief that owning luxury goods can improve his social status. (2) After providing individual counseling through Rational Emotive Behavior Therapy, both counselees I and II began to show changes. The counselees are able to use the money they have wisely.